PENGARUH JUMLAH PENDUDUK, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA DI PROVINSI BALI - Astuti, Ida Ayu Paramitha; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Development on continuous to improve the lives and well-being of all walks of life. The purpose of this study was to analyze the effect of the population, the general allocation fund and special allocation funds towards public welfare Regency/ City in the province of Bali. This research was conducted in the province of Bali with using secondary data from the years 2009-2013, the amount of data obtained by 45 observations. Data were analyzed using multiple linear analysis techniques. Based on the analysis, the general allocation fund and special allocation funds have a positive influence on people's welfare Regency / City in the province of Bali, while the number of people negatively affect public welfare Regency / City in the province of Bali. Through the analysis of the t test is known that the general allocation fund and special allocation funds have a positive influence on people's welfare Regency / City in the province of Bali, while the number of people negatively affect public welfare Regenc y / City in the province of Bali.
Keywords: population, the general allocation fund, the special allocation fund, public welfare